Storage Changes Stable Isotope Composition of Cucumbers - Horacek, Micha; Papesch, Wolfgang (Frontiers in Sustainable Food Systems, 2021)
Vegetable food stuff produced under controlled and identical conditions from one farm of 15 identical “age” (batch) has a similar isotopic composition. This fact can be used to control the 16 origin of vegetables. This question is of special relevance when food-contaminations have to 17 be traced back to the producer, or certain production claims have to be controlled. However, 18 as vegetables are harvested, brought to whole-sale merchants and to retail shops, where they 19 remain until being bought by the consumer, one has to consider possible changes in isotopic 20 composition during this transfer period, when comparing vegetables of questioned origin with 21 reference samples taken directly from the field/producer. We investigated changes in the 22 isotope composition of vegetables during storage by studying as an example cucumbers from 23 one batch. We stored the cucumbers in a vegetable storage under controlled conditions and 24 removed one sample every day and analysed its isotopic composition. We found changes in 25 the 15N and 18O isotope values over the investigated period of 21 days, with both 26 parameters showing positive linear correlations, and maximum enrichments with time of more 27 than 1.5‰ for 15N and more than 2‰ for 18O. However, within the interval the samples 28 remained in a saleable condition the isotope variations remained more or less within the 29 variability of the sample batch. Our study demonstrates that changes in the isotopic signature 30 in vegetables might occur after harvest during storage and have to be taken into account when 31 (commercial) samples collected in a market are investigated.